1981
DOI: 10.1203/00006450-198111000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Metabolism in Preterm Infants Fed Human Donor Breast Milk: the Possible Essentiality of Glycine

Abstract: SummaryNitrogen metabolism was studied in three preterm infants (mean gestation 32 wk) by the method of consecutive metabolic balance. The absorption and retention of nitrogen from breast milk was measured, and protein turnover, synthesis, and breakdown were calculated from isotopic plateau of urinary urea and ammonia using an intermittent oral administration of "N-glycine. Weight gain and nitrogen retention were compared with the weight gain and nitrogen accumulated for a foetus of equivalent gestational age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
1

Year Published

1985
1985
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 47 publications
2
52
1
Order By: Relevance
“…The researchers found that once VLBW infants regained birth weight, their average daily weight gain ranged between 14.4 and 16.1 g kg À1 per day, a rate similar to the reported intrauterine weight gain of 1.5% per day or 15 g kg À1 per day. [25][26][27][28] In addition, their average weekly increments in length (0.9 cm per week) and head circumference (0.9 cm per week) were similar to the increases in the rates of intrauterine length and head circumference reported between 26 and 36 weeks of gestation (1.1 and 0.7 cm per week, respectively). 29 This is in contrast with previous studies, in which the sickest VLBW infants had poor weight gain and inadequate catch-up growth during the first few weeks of life.…”
Section: Discussionmentioning
confidence: 71%
“…The researchers found that once VLBW infants regained birth weight, their average daily weight gain ranged between 14.4 and 16.1 g kg À1 per day, a rate similar to the reported intrauterine weight gain of 1.5% per day or 15 g kg À1 per day. [25][26][27][28] In addition, their average weekly increments in length (0.9 cm per week) and head circumference (0.9 cm per week) were similar to the increases in the rates of intrauterine length and head circumference reported between 26 and 36 weeks of gestation (1.1 and 0.7 cm per week, respectively). 29 This is in contrast with previous studies, in which the sickest VLBW infants had poor weight gain and inadequate catch-up growth during the first few weeks of life.…”
Section: Discussionmentioning
confidence: 71%
“…The measurement of 5-oxoproline (50P), L-pyroglutamic acid, in urine possibly represents just such an index. In a range of physiological and pathological conditions in which we had predicted an excessive demand for glycine, we were able to demonstrate increased urinary excretion of 50P (Jackson et al 1986).50P is a normal intermediate of the y-glutamyl cycle (Meister, 1983) and may be detected at low levels in the urine of healthy individuals. Excessive loss of 5 0 P in the urine, 5-oxoprolinuria (SOPuria), may be found in inborn errors of metabolism associated with either an increased production (glutathione synthase (EC 6.3.2.3) deficiency) or decreased utilization (5-oxoprolinase deficiency) of 50P by the body (Meister, 1978).…”
mentioning
confidence: 85%
“…A marginal state of glycine availability is probably more common than has been appreciated in the past (Jackson, 1983). Recently, we presented evidence to show that glycine might behave as a conditionally essential amino acid in the preterm human infant (Jackson et al 1981 ;Catzeflis et al1985). Furthermore, Yu et al (1985) have shown that in normal adults on a low-protein diet, glycine production in the body is insufficient to satisfy the normal metabolic demand.…”
mentioning
confidence: 99%
“…Also, during [lSN]glycine studies with preterm infants there was virtually no 15N label transferred to urea when the infants were fed on human milk, which contains low levels of protein (Jackson et al 1981;Pencharz et al 1983;Catzeflis et al 1985). This may partly reflect dilution of "N-labelled urea by any unlabelled dietary urea which is hydrolysed and recycled to urea by the mechanisms discussed previously.…”
Section: Gly Cinementioning
confidence: 99%